Sterilization impacts on marine sediment---Are we able to inactivate microorganisms in environmental samples?. Issue 12 (20th September 2018) - Otte, Julia M; Blackwell, Nia; Soos, Viktoria; Rughöft, Saskia; Maisch, Markus; Kappler, Andreas; Kleindienst, Sara; Schmidt, Caroline
ABSTRACT: To distinguish between biotic and abiotic processes in laboratory experiments with environmental samples, an effective sterilization method is required that prevents biological activity but does not change physico-geochemical properties of samples. We compared standard sterilization methods with respect to their impact on microbial abundance and activity. We exposed marine sediment to (i) autoclaving, (ii) gamma-radiation or (iii) sodium azide (NaN3 ) and determined how nucleic acids, microbial productivity, colony forming units (CFUs) and community composition of microorganisms, fungi, unicellular protists and protozoa were affected. In autoclaved and gamma-sterilized sediments, only few colonies formed within 16 days. After addition of NaN3 to the sediment, numerous CFUs (>50) but lower 3 H-leucine incorporation rates, i.e. lower protein biosynthesis rates, were found compared to the other two sterilization techniques. Extractable RNA was detected immediately after all sterilization treatments (0.2–17.9 ng/g dry sediment) but decreased substantially by 84%–98% after 16 days of incubation. The total organic carbon content increased from 18 mg L −1 to 220 mg L −1 (autoclaving) and 150 mg L −1 (gamma-radiation) after sterilization. We compare advantages and disadvantages for each tested sterilization method and provide a helpful decision-making resource for choosing the appropriate sterilization technique for environmental studies, particularly for marine sediments. Abstract : Different sterilization techniques (autoclaving, gamma-sterilization and addition of NaN3 ) of natural sediment samples are compared and are shown to perform quite distinctly in decreasing microbial activities and eliminating signatures of microbial life.